Integration Of Economic Principles In Business Administration: A Theoretical Analysis - Irgashev , Akmaljon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the fundamental relationship between economic theory and business administration practices, analyzing how economic principles inform managerial decision-making and organizational strategy. The research results demonstrate that successful business administration requires economic reasoning to be applied in both strategic planning and financial management and competitive positioning activities.